ANALISIS FRAUD BANK, PENEGAKAN HUKUM PERBANKAN, DAN PERAN OJK DALAM PENGAWASAN BPR - Danny Trisno Susetyo; Aditya Fajri Kurnia Pradana (Tahta Media Group, 2024)
Banks serve as intermediaries between savers and borrowers, collecting funds from the public and providing credit. To maintain trust, banks must apply prudential banking principles in lending, including knowing who the prospective debtor is through the